Flow behavior over well-escape weirs - Hassan I. Mohamed; Gamal Abozeid; Nashat A. Ali; Wagdy M. Saied (Water Science, 2024)
Weirs play an important role in controlling and managing water in irrigation canal networks through several functions, such as discharge measurements, water distribution, and lowering the water level. Weirs also play a crucial role in protecting canals from flooding, which might cause the earthen banks to collapse, by eliminating surplus water at the ends of the canals. Over the previous decades, the flow over the traditional sharp-crested weirs was extensively investigated by many researchers; however, the well-escape weirs have not received sufficient attention. These types of weirs were mostly constructed in the form of vertical wells that may be circular or rectangular in shape, and water may flow through the entire perimeter of the weir or part of the perimeter. In the present research, the effect of the well-escape-weir shape on the characteristics of flow over the weir was studied. A set of models were constructed in different shapes, circular and square, and the entire perimeter of the weir or part of the perimeter is working as the weir crest length. The discharge passing over the unit length of the weir crest (q) is investigated and compared for the circular and square weirs of various crest lengths and positions. The results indicated that the discharge capacity of the circular weirs increases by a rate ranging between 7.5% and 15% more than that of the square weirs at the same head. Also, results indicated that the discharge coefficient of the circular weirs increases by a rate ranging between 9.3% and 10.3% more than that of the square weirs. This behavior can be attributed to the interference between the orthogonal water nappes at the corners of the square models. In addition, the flow direction has little effect on the discharge coefficient at small discharges, and this effect becomes more obvious at higher discharges. Additionally, the well-escape weirs of the upstream crest have a slightly higher discharge capacity than those of the downstream crest due to the effect of the approach velocity, which increases the water entrance velocity at the upstream crest. The results of flow patterns around the weir showed that the locations of maximum flow velocities (u, v, w) are mostly near the weir crest and depend entirely on the crest length and position.